An Approach for Implicitly Detecting Information Needs - White, Ryen W.; Jose, Joemon M.; Ruthven, Ian (12th International Conference on Information and Knowledge Management (CIKM 2003), New Orleans, U.S.A., 2003)
Searchers can have problems devising queries that accurately express their, often dynamic, information needs. In this paper we describe an adaptive approach that uses unobtrusive monitoring of interaction to help alleviate such problems and support searchers in their seeking. The approach we propose implicitly selects terms to better represent information needs, gathers evidence on potential changes in these needs, and uses this evidence to tailor the result presentation accordingly. A user evaluation of an interface implementing our approach, presented in [7], shows it can select terms that approximate current information needs and provide evidence to track changes in these needs.